BANGKITNYA PAHAM KOMUNIS DI INDONESIA - Firdaus Firdaus (TEXTURA, 2022)
The reforms in 1998  resulted in the fall of the New Order government under the leadership of President Suharto. The New Oreder government was anti-communist and did not provide space for communists to live in the Unitary State of Republic of Indonesia. With the fall of The New Order, freedom of speech and the establishment of political parties were granted. Therefore, the People’s Democratic Party (FRD) under the leadership of Budiman Sudjatmoko, Who since the New Order era has always criticized the policies of the New Order government. FRD registeres itsel In its development, FRD changed its strategy, namely that most of the members spread out and entered major political parties such as the Indonesia Democratic Party of Struggle (PDIP) and other nationalist-based political parties. By joining major political parties, many former FRD members sat in the People’s Reoresentative Council (DPR). After they sat in the DPR, especially after the PDIP won 2014 general election, many DPR product were controversial in the life of society and the nation, such as the  Draft Law (RUU) for the path of Pancasila Ideology (BPIP) in 2020. These two bills have caused controversy because they are alleged to have revived Bung Karno’s teachings, namely the Nasakom ( Religious Nationalist and Comunist) concept.